The Geoeffectiveness of Solar Wind Current Sheets and Its Modulation by Foreshock Ions - Boyi Wang; Yi Wang; Terry Z. Liu; Vassilis Angelopoulos (Geophysical Research Letters)
Abstract We examined the evolution of 34 solar wind bifurcated current sheets in the magnetosheath and their magnetospheric responses, using the in‐situ observations of the THEMIS probes and the GOES satellites. The role of foreshock ions in that process is also determined. The first current sheet event did not exhibit any modulation by foreshock ions; it generated a dynamic pressure plateau, which further evolved into a dynamic pressure plateau in the magnetosheath and likely generated mirror mode waves in the magnetosphere. The second event exhibits foreshock ions which enhanced the perturbations in the current sheet due to the disappearance and reappearance of foreshock ions controlled by the direction changes of magnetic field. That current sheet further compressed the magnetosphere and drove stronger magnetic field oscillations than the first event. Thus, solar wind current sheets can be geoeffective and their geoeffectiveness can be amplified by the foreshock ions inside their structures.